Domus method for predicting sunlit areas on interior surfaces - Rocha, Ana Paula de Almeida; Mendes, Nathan; Oliveira, Ricardo C. L. F. (Ambiente Construído, 2018)
This pilot study aims to analyze the solar radiation transmission, daylight performance and glare reduction probability of complex shape solar control devices, developed with parametric modeling and digital fabrication. As methodology, initially the Rhinoceros3D+Grasshopper digital tools suite was used for the parametric modeling of solar control devices. Performance evaluations were performed by computational simulation and measurements in prototypes. For the simulations, the Diva-for-Rhino and Ladybug plug-ins were used. For the measurements, through digital fabrication, a prototype used for glare evaluations through HDR photographs was made. As main results, the solar control devices contributed to the control of solar radiation admission, better daylight distribution and glare reduction in the indoor analysis environment, confirming the reliability of the methodological procedures employed. It is important to highlight the effects of depth and inclination of the devices analyzed, respectively on the daylight distribution and selectivity in the admission of solar radiation between winter and summer. Finally, the shading masks show that despite all the development of modeling and simulation tools, the simple understanding of the solar geometry is still essential for the adequate performance of the solar control devices.